The Emergence of Embryos from Hard Seeds is Related to the Structure of the Cell Walls of the Micropylar Endosperm, and not to Endo-β-mannanase Activity - GONG, XUEMEI (Ann Bot, 2005)
• Background and Aims Seeds of carob, Chinese senna, date and fenugreek are hard due to thickened endosperm cell walls containing mannan polymers. How the radicle is able penetrate these thickened walls to complete seed germination is not clearly understood. The objective of this study was to determine if radicle emergence is related to the production of endo-β-mannanase to weaken the mannan-rich cell walls of the surrounding endosperm region, and/or if the endosperm structure itself is such that it is weaker in the region through which the radicle must penetrate. • Methods Activity of endo-β-mannanase in the endosperm and embryo was measured using a gel assay during and following germination, and the structure of the endosperm in juxtaposition to the radicle, and surrounding the cotyledons was determined using fixation, sectioning and light microscopy. • Key Results The activity of endo-β-mannanase, the major enzyme responsible for galactomannan cell wall weakening increased in activity only after emergence of the radicle from the seed. Thickened cell walls were present in the lateral endosperm in the hard-seeded species studied, but there was little to no thickening in the micropylar endosperm except in date seeds. In this species, a ring of thin cells was visible in the micropylar endosperm and surrounding an operculum which was pushed open by the expanding radicle to complete germination. • Conclusions The micropylar endosperm presents a lower physical constraint to the completion of germination than the lateral endosperm, and hence its structure is predisposed to permit radicle protrusion.